Come il ragno a Nazca: per un’archetipologia junghiana dell’aracnide in Dino Buzzati, Tommaso Landolfi e Primo Levi - Caterina Caiola (Status Quaestionis, 2024)
The following article explores the archetypal poignancy of the spider in twentieth-century Italian literature by analyzing the stories of Tommaso Landolfi, Primo Levi and Dino Buzzati. Despite their distinct poetics, they simultaneously used various kinds of animal figures sostructurally throughout their careers, that it makes sense to investigate the actual bestiaries derived from their productions. The weight that magical and primitive culture, as well as their individual psychology, had in this phenomenon will be investigated and culturally motivated, through a study that aims to probe our collective imagination, somewhere between the definition given by psychoanalyst Jung and the reconstruction of folk beliefs given by anthropologists such as De Martino. Not by chance, we propose the spider as emblematic to our mythical-ritual system of inquiry, as well as one of the most significant archetypal animal images in literature, magic, phobia, and folklore.